A History of Malawi, 1859-1966 - McCracken, John, 1938- (James Currey ; Boydell & Brewer, 2012)
This is the first comprehensive history of Malawi during the colonial period. Using a wide range of primary and secondary sources, John McCracken places this history within the context of the pre-colonial past. Central themes are the shaping of the colonial economy, the influence of Christianity, resistance to colonial occupation and the rise of a powerful nationalist movement that contained within it the seeds of a new authoritarianism. In particular, the author demonstrates the interrelationship between environmental and economic change and the impact these forces had on the Malawian peasant.